Weight, Rather Than Obesity Distribution, Explains Peak External Knee Adduction Moment During Level Gait - Segal, Neil A. (2009)
OBJECTIVE: To determine whether a lower-body obesity pattern increases estimated forces on the medial compartment of the knee joint. DESIGN: Cross-sectional clinical biomechanical study. RESULTS: Nineteen normal weight (body mass index, 22.8 ± 1.8 kg/m(2)), 20 centrally obese (body mass index, 35.0 ± 4.0 kg/m(2) and waist-hip ratio ≥0.85 for women; ≥0.95 for men), and 20 lower-body obese (body mass index, 36.4 ± 5.4 kg/m(2)) adults aged 37–55 yrs and without knee pain were recruited. There were no intergroup differences for age. Weight did not differ between obese groups, but thigh girth differed between groups (P < 0.0001). In univariate analysis, both obesity group and thigh girth were significantly related to peak external knee adduction moment in mid-stance phase. However, in multivariate analysis after adjusting for weight, no statistically significant differences persisted using either obesity distribution or thigh girth as predictors. Weight was a significant predictor of external knee adduction moment, explaining 33% (P < 0.0001) of variance in external knee adduction moment for level gait. CONCLUSIONS: These data do not support a significant difference in knee medial compartment loading based on obesity distribution, but do support greater torque with higher weight. This suggests that the mechanism of obesity increasing risk for knee osteoarthritis may not be related to obesity distribution.